Exceptional enhancement of ductility and toughness in poly(vinylidene fluoride)/carbon nanotubes composites. Issue 26 (26th March 2016) - Chen, Xuelong; Liang, Yen Nan; Yin, Ming; Roy, Sunanda; Marom, Gad; Men, Yongfeng; Hu, Xiao
ABSTRACT: The reinforcement of mechanical properties of polymeric materials is often important for widening their applications; however, it remains a technical challenge to effectively increase toughness without degrading stiffness and strength of the polymers. In this work, by a facile methodology combining solution mixing and melt blending, poly(vinylidene fluoride)/multi‐walled carbon nanotubes (PVDF/MWCNTs) composite with exceptionally enhanced ductility and toughness are prepared. With only 0.2 wt % CNT loading, the elongation at break has increased from originally 138% to almost 500%, while toughness improved by as much as 386%, without compromising the stiffness and strength. Note that raw CNTs are directly dispersed in the matrix without any surface modification. In order to elucidate this novel enhancement of ductility of PVDF/MWCNTs composites, we carried out detailed analyses based on results from ultra‐small‐angle X‐ray scattering (USAXS), cryo‐fractured surface morphology, differential scanning calorimetry (DSC), and Fourier transform infrared spectroscopy (FTIR). It is proposed that the enhanced ductility are contributed by a synergistic combination of "void pinning effect" of CNT, as well as the formation of γ phase polymorph as the interphase in the PVDF/CNTs composites. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43610. Abstract :